В решении.
Пошаговое объяснение:
1) -5 * 49 * 4 = (-5 * 4) * 49 = (-20) * 49 = -980;
2) -0,2 * 3,8 - 3,7 * (-0,2) = (-0,2) * (3,8 - 3,7) = (-0,2) * 0,1 = -0,02;
3) -3/7 * (-2/3) * 2 1/3 * (-2 1/4) =
= -3/7 * (-2/3) * 7/3 * (-9/4) =
= ((-3/7) * 7/3) * ((-2/3) * (-9/4)) =
= (-1) * 3/2 = -3/2 = -1,5;
4) (-2/3 + 2 4/9) * 9 =
= (-2/3 + 22/9) * 9 =
= -6 + 22 = 16;
5) (2х + 0,2х)*(х - 0,5) = 0
2,2х * (х - 0,5) = 0
2,2х² - 1,1х = 0 неполное квадратное уравнение
2,2х*(х - 0,5) = 0
2,2х = 0
х₁ = 0;
х - 0,5 = 0
х₂ = 0,5.
11 2/3-8 3/4=35/3-36/4=(140-108)/12=32/12=8/3
3 1/3+2 5/6=10/3+17/6=37/6
8/3+37/6=53/6
53/6-4 7/12=53/6-57/12=(106-57)/12=49/12=4 1/12